2010
DOI: 10.1111/j.1469-0691.2009.02966.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary investigation of 31 infants with suspected congenital rubella syndrome in Sudan

Abstract: Between 2005 and 2006, clinical specimens were collected from 31 infants with suspected congenital rubella syndrome (CRS) who presented at six hospitals in Khartoum, Sudan. Eleven (35.5%) were laboratory confirmed as CRS cases by testing for anti-rubella IgM, IgG and viral genome. For the first time in Sudan, the rubella virus genome was directly detected in clinical specimens of six CRS cases and two viruses were isolated in cell culture. Phylogenetic analysis suggested that three genotypes of rubella virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…This result does not exclude the risk of CRS in our population, as CRS can occur even when susceptibility levels are below 10% [13]. In accordance with this fact, we have recently documented the occurrence of CRS in Sudan, when 11 CRS case were laboratory confirmed in a hospital-based study during June 2005 to May 2006 [6]. Consequently, it is highly recommended to assess the burden of CRS in Sudan because a high number of CRS cases might occur if this low susceptibility is due to recent rubella outbreaks.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This result does not exclude the risk of CRS in our population, as CRS can occur even when susceptibility levels are below 10% [13]. In accordance with this fact, we have recently documented the occurrence of CRS in Sudan, when 11 CRS case were laboratory confirmed in a hospital-based study during June 2005 to May 2006 [6]. Consequently, it is highly recommended to assess the burden of CRS in Sudan because a high number of CRS cases might occur if this low susceptibility is due to recent rubella outbreaks.…”
Section: Discussionmentioning
confidence: 51%
“…Rubella vaccine is not included in the Sudanese national immunization programme, and data on the prevalence of rubella among women of childbearing age are inadequate [5]. Furthermore, there is no routine surveillance for CRS, and data on its incidence are extremely scarce [6]. Sudanese surveillance for measles and rubella since 2006 has reported that rubella infection is a frequent cause of none-measles rash [7].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we identified CRS in 11 Sudanese infants using ELISA, reverse transcriptase-PCR and rubella virus isolation [9]. Another recent study identified seven cases of congenital rubella infection among 92 newborns in Khartoum based on ELISA testing of cord blood [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, neither routine CRS surveillance nor rubella vaccination is available and data on CRS are inadequate. We documented the occurrence of CRS in Sudan for the first time in 2010 [9] and reports about rubella seroprevalence among pregnant women are available from some Sudanese states including Khartoum State [10] and West Sudan [11]. The present study aimed to identify CRS cases among Sudanese infants presented at different hospitals in Khartoum to obtain more information about the CRS situation in Sudan.…”
Section: Introductionmentioning
confidence: 99%
“…Genotype assignments were made using an alignment of sequences from the DRC and the 32 WHO reference virus sequences [WHO, 2013] using the neighbor joining algorithm of the MEGA6 program [Tamura et al, 2013]. Rubella sequences from the neighboring countries of Sudan [Omer et al, 2010], Uganda [Namuwulya et al, 2014], and Tanzania [Centers-for-Disease-Control-and-Prevention, 2013] were also used in this analysis. Rubella sequences from this study were deposited on GenBank under accession numbers KU218397-KU218404.…”
Section: Methodsmentioning
confidence: 99%